A noninvasive ultrasonic method for the elasticity evaluation of the carotid arteries and its application in the diagnosis of the cerebro-vascular system - POWAŁOWSKI, Tadeusz; PEŃSKO, Bogumił (Archives of Acoustics, 1988)
This study presents a comparative evaluation of the methods applied so far to describe the elasticity of the blood vessel walls. It was shown that one of the possible solutions in the description of the dependence between the vessel cross-section and the blood pressure is a logarithmic function. The authors assumed the logarithmic wall rigidity coefficient a resulting from this function as the index of the mechanical properties of the walls of the carotid arteries examined. The value of this coefficient was determined noninvasively from the ultrasonic measurement of the instantaneous diameter of the common carotid artery and the systolic and diastolic pressures measured with a manometer in the brachial artery. The studies were carried out for a group of 43 healthy persons aged between 9 and 64, and for a group of 9 persons aged between 53 and 62 in whom arteriosclerotic changes were found by the X-ray arteriography in the extracranial carotid arteries. The results obtained indicate a linear increase in the coefficient a with age of healthy persons. For the ill group the mean value of the coefficient a was about 50% higher than that for the healthy in the same age group.